Towards a common definition of hospital-acquired deconditioning in adults: a scoping review - Katie Robinson; Alison Cowley; Meri Westlake; Adam L. Gordon (BMJ Open)
Background Hospital-acquired deconditioning is a term used in clinical practice, describing a loss of physical and/or cognitive function associated with hospitalisation. Previous reviews have addressed interventions, its prevalence in older adults and potential assessment tools. However, each review has reported a core limitation, the need for an agreed-upon definition and diagnostic criteria for hospital-acquired deconditioning.Objective We aimed to identify key components used to define hospital-acquired deconditioning in adults. We sought to do this by identifying diagnostic criteria, describing how authors operationalised Hospital- Acquired Deconditioning (HAD), and describing differences between HAD and other immobility-linked syndromes. This article focuses on how hospital-acquired deconditioning is understood and operationalised.Design A scoping review using the Joanna Briggs Institute methodology for evidence synthesis.Eligibility criteria Published in English after 1 January 1990, investigating adults over 18, set in inpatient rehabilitation or acute care settings, and including either a definition or description of hospital-acquired deconditioning or an outline of strategies to assess, prevent or manage hospital-acquired deconditioning.Sources of evidence Published and grey literature, no restriction was placed on study design.Charting methods Relevant data, where available, was extracted from each source using a proprietary data extraction template.Results One hundred and three articles were included from 2403 retrieved results. Thirty-three were from rehabilitation or post-acute care settings, 53 from acute care, 15 from intensive care and two from other settings. The literature was diverse in methodology and research question addressed. Hospital-acquired deconditioning was poorly defined, no consistent patterns were identified in aetiology and sequelae; diagnostic criteria were not fully agreed on.Conclusions The literature on hospital-acquired deconditioning is large, diverse and incomplete. Further work is required to develop a shared definition of hospital-acquired deconditioning, enabling researchers to coalesce for better understanding of the phenomenon, and clinicians, in turn, to better treat and mitigate against it.Review registration OSF: https://osf.io/b5sgw/